2008
DOI: 10.1530/rep-07-0461
|View full text |Cite
|
Sign up to set email alerts
|

Pro-labour myometrial gene expression: are preterm labour and term labour the same?

Abstract: Preterm labour (PTL) is the most important cause of neonatal morbidity and mortality. While some causes have been identified, the mechanisms involved remain elusive. This study investigates whether term labour (TL) is an appropriate model for PTL by examining prolabour gene expression, using quantitative rtPCR, and protein synthesis, using Western analysis, in preterm and term myometrial samples obtained from the upper and lower uterine segments before and after the onset of labour. In the lower segment, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
62
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 55 publications
(54 reference statements)
8
62
0
Order By: Relevance
“…13 In parallel, upregulation of pro-inflammatory cytokines mRNA expression of Interleukin-1 b (IL-1b, IL-6, C-X-C motif ligand (CXCL) 8 and C-C motif ligand (CCL) 2 was observed in the myometrium of healthy labouring women. [14][15][16][17][18] Our recent data confirmed these findings and revealed a more extensive list of up-regulated cytokine and chemokine proteins (CXCL8, CXCL1, CCL2, CCL7, IL-9, IL-18, IL-1RN, tumor necrosis factor alpha (TNFa) and granulocyte colony-stimulating factor (G-CSF)) in healthy TL human myometrial tissue samples, while also detecting a higher number of macrophage and neutrophil infiltrate. 7,19 The trigger that elevates cytokines in the myometrium of healthy women during labour remains largely elusive.…”
Section: Introductionsupporting
confidence: 77%
“…13 In parallel, upregulation of pro-inflammatory cytokines mRNA expression of Interleukin-1 b (IL-1b, IL-6, C-X-C motif ligand (CXCL) 8 and C-C motif ligand (CCL) 2 was observed in the myometrium of healthy labouring women. [14][15][16][17][18] Our recent data confirmed these findings and revealed a more extensive list of up-regulated cytokine and chemokine proteins (CXCL8, CXCL1, CCL2, CCL7, IL-9, IL-18, IL-1RN, tumor necrosis factor alpha (TNFa) and granulocyte colony-stimulating factor (G-CSF)) in healthy TL human myometrial tissue samples, while also detecting a higher number of macrophage and neutrophil infiltrate. 7,19 The trigger that elevates cytokines in the myometrium of healthy women during labour remains largely elusive.…”
Section: Introductionsupporting
confidence: 77%
“…The involvement of prostaglandins and proinflammatory cytokines 17 has been suggested as a potential mechanism. It is possible that the elevation in the apoptosis rate induced by potent GVC-MVs bearing significant amounts of concentrated inflammatory cytokines, as revealed in our study, contribute in part to early delivery observed in women with GVCs.…”
Section: Discussionmentioning
confidence: 99%
“…It induces basal and store-operated calcium entry in myometrial smooth muscle cells (Tribe et al 2003), thus directly enhancing their contractile potential. IL1B can also increase the production of pro-inflammatory cytokines and chemokines; promote the production of prostaglandins via PTGS2, mediators of uterine contractions; and matrix metalloproteinases (MMPs) which activate cervical ripening and foetal membrane rupture, events culminating in successful labour and delivery (Roh et al 2000, Bowen et al 2002, Keelan et al 2003, Lappas & Rice 2004, Christiaens et al 2008, Tattersall, et al 2008. The findings of this study demonstrate that RAF1 is involved in the genesis of pro-inflammatory and RAF1 and labour in myometrium pro-labour mediators induced by IL1B.…”
Section: Discussionmentioning
confidence: 78%
“…Human labour is associated with increased concentrations of IL1B in both gestational tissues and biological fluids (Elliott, et al 2001, Bowen et al 2002, Tattersall et al 2008, and intra-amniotic and/or systemic administration of IL1B to mice and monkeys induces preterm labour (Romero et al 1991, Romero & Tartakovsky 1992, Sadowsky et al 2006. IL1B is thought to contribute to the onset of labour by stimulating and potentiating uterine contractions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation